KNOWLEDGE NEEDS OF SPINAL INJURY SURGERY PATIENTS BEFORE DISCHARGE AT THE SPINAL SURGERY DEPARTMENT OF VIET-DUC UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the knowledge needs of patients undergoing spinal injury surgery before discharge from the Spine Surgery Department of Viet Duc University Hospital. Method: A cross-sectional descriptive study was conducted among 150 patients undergoing spinal surgery in the Spine Surgery Department at Viet Duc Friendship Hospital to assess their knowledge needs using the Patient Learning Needs Scale (PLNS). Results: The total PLNS score was 161,48 ± 5,78. Patients had the highest need for knowledge regarding care, detection of complications, and signs of disease (4,28 ± 0,78). This was followed by a high need for expertise in medication (4,17 ± 0,89) and information about treatment and daily activities (4,00 ± 0,87). The need for knowledge related to the disease itself was lower (3,93 ± 0,91), and the lowest need was for knowledge about community support and care (3,82 ± 1,03). Conclusion: The knowledge needs of 150 spine surgery patients were high. Recommendation: The assessment of patients’ knowledge needs should be strengthened and integrated into clinical practice, especially nursing practice, to contribute to comprehensive postoperative care.